PERSEPSI INVESTOR SEBAGAI PEMODERASI PENGARUH PROFITABILITAS PADA RESPON PASAR - Avelia, Bertha; Ardiana, Agus (E-Jurnal Akuntansi, 2016)
This study aimed to examine the effect of profitability to market response and investor’s perception as moderating variables. This research was conducted in all company listed on the Stock Exchange in 2011-2014. The total of sample is 449 companies. The sampling method is nonprobability sampling method with purposive sampling technique. The analysis technique is Moderated Regression Analysis (MRA). This study shows that profitability have positive effect to market response and investor’s perception capable of reinforcing positive effect of profitability to market response. The companies that report gain in their financial statement, tend to get positive response from investor then many of them want to buy stock from that company and with investors who perceive that report as good news, so the market response will be more positive.
Keywords: Investor' s Perception, Profitability, Market Response